Floquet chiral edge states in graphene - Pérez Piskunow, Pablo Matías (2014)
We report on the emergence of laser-induced chiral edge states in graphene ribbons. Insights on the nature of these Floquet states is provided by an analytical solution which is complemented with numerical simulations of the transport properties. Guided by these results we show that graphene can be used for realizing non-equilibrium topological states with striking tunability: While the laser intensity can be used to control their velocity and decay length, changing the laser polarization switches their propagation direction.